PENYELUNDUPAN HUKUM PERKAWINAN BEDA AGAMA DI INDONESIA - Ade Witoko, Prasetyo; Budhisulistyawati, Ambar (HUKUM PEMBANGUNAN EKONOMI, 2019)
Abstract  This article aims to find out about interfaith marriage arrangements carried out through legal  smuggling in Indonesia. This study is a descriptive doctrinal legal research. Data sources from this article are in the form of primary legal material and secondary legal material. The technique of collecting legal material in this article is the library study technique. The approach in this  research is the legislative approach. The result of the article is that marriage according to the  Marriage Law is a marriage carried out according to each religion and belief. So that marriage is considered valid if according to the religion and beliefs of each prospective husband and wife is also valid. Every religion cannot authorize interfaith marriages, because all religions want their followers to marry the same religion, it can be concluded that interfaith marriages are not legal, because they are not in accordance with the contents of the Marriage Law, namely marriage is valid if carried out according to each religion -one, then avoidance of the law that should apply or can be said to be an act of legal smuggling.Keywords: Marriage; Different Religion Marriage; Law SmugglingAbstrakArtikel ini bertujuan untuk mengetahui mengenai pengaturan perkawinan beda agama yang  dilakukan melalui penyelundupan hukum di Indonesia. Penelitian ini adalah penelitian hukum doktrinal bersifat deskriptif. Sumber data dari artikel ini yaitu berupa bahan hukum primer dan bahan hukum sekunder. Tehnik pengumpulan bahan hukum dalam artikel ini adalah tehnik studi kepustakaan. Pendekatan dalam penilitian ini adalah pendekatan perundang-undangan. Hasil artikel yaitu perkawinan menurut Undang-Undang Perkawinan adalah perkawinan yang dilaksanakan menurut agama dan kepercayaan masing-masing. Sehingga perkawinan dianggap sah jika menurut agama dan kepercayaan masing-masing calon suami istri tersebut juga sah. Setiap agama tidak bisa mengesahkan perkawinan beda agama, karena semua agama menginginkan umatnya untuk menikah dengan yang seagama, maka dapat disimpulkan bahwa perkawinan beda agama tidak sah, karena tidak sesuai dengan isi Undang-Undang Perkawinan yaitu perkawinan adalah sah apabila dilaksanakan menurut agama dan kepercayaan masing-masing, maka dilakukan penghindaran terhadap hukum yang seharusnya berlaku atau dapat dikatakan sebagai tindakan penyelundupan hukum.Kata Kunci : Perkawinan; Perkawinan Beda Agama; Penyelundupan Hukum